Postoperative sepsis-associated neurocognitive disorder: mechanisms, predictive strategies, and treatment approaches - Zijing Gao; Zhenyu Xu (Frontiers in Medicine)
Sepsis is a critical condition characterized by an abnormal immune response to infection, resulting in systemic inflammation, organ failure, and high mortality rate. Postoperative sepsis, accounting for nearly one-third of all sepsis cases, predominantly affects the elderly and individuals with pre-existing conditions, with fatality rates between 30 and 50%. Surgical stress induces immune, hormonal, and metabolic disturbances, heightening susceptibility to immune dysregulation and sepsis. Neurocognitive disorders related to postoperative sepsis, which share pathophysiological similarities with sepsis-associated encephalopathy, involve neuroinflammation, blood–brain barrier disruption, and mitochondrial dysfunction. Cognitive impairments, such as delirium, are frequent postoperative complications that vary in severity depending on the surgical complexity. This review examined the underlying mechanisms of these dysfunctions, the influence of different surgical procedures, and predictive and therapeutic strategies, including machine learning models, aimed at improving patient outcomes.